Przekształcenia w zakresie cenzury filmowej w Japonii do końca II wojny światowej - Głownia, Dawid (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article discusses the transformations in film censorship and film policy in Japan until the end of World War II. Its first part outlines the general trend of these changes – gradual centralization of film censorship and increased scope of state control over film. The next sections are devoted to film regulations from 1917, 1925 and 1939 and other tools of government influence over cinema in Japan. The main conclusion of the article is that the censorship criteria in each of the regulations discussed were formulated in general terms which could be interpreted in accordance with the immediate interests of the authorities and state bureaucracy.